Sensor redundancy based FDI using an LPV sliding mode observer. Issue 14 (1st September 2018) - Chen, Lejun; Edwards, Christopher; Alwi, Halim
Abstract : In this study, a linear parameter varying (LPV) sliding mode sensor fault detection and isolation (FDI) scheme is proposed wherein knowledge of the measurement redundancy is utilised to achieve FDI in multiple channels simultaneously. Such a situation is common in some state‐of‐the‐art aircraft fault diagnosis systems where information is generally/mainly measured based on triplex redundancy. The scheme proposed in this study is based on an LPV sliding mode observer and exploits the so‐called equivalent output error injection signal to create estimates of the measurement faults. In the case of sensor measurement redundancy, and where there exists a fault‐free (but unknown) sensor amongst the set of measurements, the fault reconstruction performance of the observer can be improved by isolating and using the output error injection signal associated with the fault‐free redundant sensor. Simulation results using the RECONFIGURE benchmark model demonstrate the effectiveness of the scheme.